ANALISIS FRAMING PEMBERITAAN KEKERASAN SEKSUAL PADA PEREMPUAN DI MEDIA ONLINE - Wilda Hikmalia; Hafied Cangara; Umaimah Wahid (Jurnal Ranah Komunikasi, 2022)
This study aims to examine the tendency of online media coverage of cases of sexual violence experienced by women, especially in this study the case of Novia Widyasari, a student in Mojokerto, East Java. The online media, which are considered to have not given special attention to these cases. The production of texts in news tends to be far from positioning women as victims of sexual violence. The research method uses Robert N. Entman's framing analysis with a critical paradigm to disassemble the production of texts in online media that present news related to sexual violence. The object of research regarding cases of violence against women was taken from three online media, namely suara.com, kompas.com, and cnnindonesia.com with a system of choosing one news item to represent. The results show that not all media can provide a frame that fits the case of violence. The balance of news related to cases of sexual violence experienced by Novia Widyasari from media institutions is refraction. On the news side, there is a protrusion of the victim, namely as a woman and receiving sexual treatment. The news strengthens the cultural ideology in which women are considered to be the weakest.